The Influence of Training and Work Discipline on the Performance of Human Capital Division Employees at PT XYZ - Bintang A. Sentani Lubis; Mochamad Vrans Romi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
PT XYZ is a company engaged in the pharmaceutical and health product distribution business. Internal company data shows gaps in training programs and suboptimal employee attendance rates. These conditions indicate the need to evaluate the effectiveness of training and the implementation of work discipline as efforts to improve employee performance. This study aims to determine the effect of training and work discipline on employee performance at PT XYZ. The research method used is a quantitative approach with data collection techniques through interviews and questionnaires. Data analysis was performed using quantitative descriptive and quantitative associative methods with multiple linear regression analysis techniques through data processing using SPSS version 27. There were 41 respondents in this study, consisting of employees from the human capital division at PT XYZ. The results of the study show that: (1) training does not affect the performance of employees in the human capital division at PT XYZ, (2) work discipline has a positive effect on the performance of employees in the human capital division at PT XYZ, and (3) training and work discipline simultaneously affect the performance of employees in the human capital division at PT XYZ. Based on these research results, it can be concluded that the company needs to consistently improve the implementation of work discipline and evaluate training programs to provide tangible contributions to the company's performance.